Use of Intravitreal Dexamethasone Implant in Patients with Cataract and Macular Edema Undergoing Phacoemulsification. Issue 2 (March 2015) - Sze, Amy M.; Luk, Fiona O.; Yip, Terri P.; Lee, Gary K.; Chan, Carmen K.
Purpose: To study the safety and efficacy of intravitreal dexamethasone implant in patients with cataract and macular edema undergoing phacoemulsification and intraocular lens (IOL) implantation. Methods: Twenty-four eyes with macular edema secondary to diabetic retinopathy (diabetic macular edema [DME]) and retinal vein occlusion (RVO) were retrospectively reviewed. These eyes underwent phacoemulsification with IOL implantation and intravitreal dexamethasone implant 0.7 mg at the same setting between September 2012 and September 2013. Demographic data, best-corrected visual acuity (BCVA), central macular thickness (CMT), intraocular pressure (IOP), surgical time, and complications were recorded. Results: Twelve eyes had DME and 12 eyes had RVO (10 central RVO and 2 branch RVO). Median baseline logMAR BCVA was 1.0 (Snellen 20/200) and mean baseline CMT was 530.2 ± 218.9 µm. Median follow-up duration was 13 months. At last follow-up, median visual acuity improved significantly to 0.523 (Snellen 20/66) (p = 0.003) and CMT decreased to 300.7 ± 78.1 µm (p = 0.000). Median surgical time was 23 minutes. There were no intraoperative complications. In 12 eyes, macular edema recurred, requiring further treatment, and median time to recurrences was 21 weeks. One eye had raised IOP after second dexamethasone implant for recurrent macular edema. No major complication such as vitreous hemorrhage, retinal detachment, or endophthalmitis occurred. Conclusions: Combined cataract surgery with intravitreal dexamethasone implant seems to be safe and effective in treating patients with cataract and macular edema in this small case series. A larger prospective study with longer follow-up is necessary to demonstrate the long-term benefit of this combined procedure.